2015
DOI: 10.1136/annrheumdis-2014-205897
|View full text |Cite
|
Sign up to set email alerts
|

Digital ulcers predict a worse disease course in patients with systemic sclerosis

Abstract: In patients with SSc, HDU at presentation predicts the occurrence of DUs at follow-up and is associated with cardiovascular worsening and decreased survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 17 publications
3
93
0
4
Order By: Relevance
“…A recent study by D’Alto et al [16] reported a significant worsening of sPAP (from 26.1 ± 6.0 to 28.8 ± 6.3) after a 3-year follow-up in a group of 74 consecutive SSc patients, in which IV iloprost was administered in 19% of cases. In the EUSTAR cohorts, where the treatment with IV iloprost is reported in 15.6% of cases [17], overall survival at 5 years is generally comprised between 80 and 90% [15, 18, 19]. Therefore, our results can be considered encouraging.…”
Section: Discussionmentioning
confidence: 57%
“…A recent study by D’Alto et al [16] reported a significant worsening of sPAP (from 26.1 ± 6.0 to 28.8 ± 6.3) after a 3-year follow-up in a group of 74 consecutive SSc patients, in which IV iloprost was administered in 19% of cases. In the EUSTAR cohorts, where the treatment with IV iloprost is reported in 15.6% of cases [17], overall survival at 5 years is generally comprised between 80 and 90% [15, 18, 19]. Therefore, our results can be considered encouraging.…”
Section: Discussionmentioning
confidence: 57%
“…Nevertheless, the persistence of defined skin sclerosis is not consistent with inactive disease. Digital ulcers are clearly related to vascular disease activity and have been recently found to predict the occurrence of new digital ulcers during follow-up and to be associated with cardiovascular morbidity and decreased survival 35. A decreased DLCO can depend on both vascular and interstitial lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…Digital ulcers are the consequence of an ischemic injury leading to necrosis of skin and subcutaneous tissues. The presence of DU is associated with increased burden and disability, reduced quality of life, impairment of daily activities, and decreased survival [5–7]. …”
Section: Introductionmentioning
confidence: 99%